A PRACTICAL USING OF THE QUEST PROGRAM TO ANALYZE THE CHARACTERISTICS OF THE TEST ITEMS IN EDUCATIONAL MEASUREMENT - Ikhsanudin Ikhsanudin; Novaliah Novaliah; Hidayatullah Hidayatullah; Memi Almizi (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2023)
This study aims to analyze an assessment instrument, mainly the characteristics of the test items, by using a Quest program. This study is a descriptive quantitative study in one school in Yogyakarta. The focus of this study was fifty items of the teacher-made test. The items have been tested on 316 students. The analysis results show that items of the teacher-made test have various difficulty levels and discrimination indexes. A range of item difficulty levels is between 0.01 to 0.99 based on classical analysis and between -3.20 to 7.32 based on the Rasch model. All items of that test have a positive discrimination index and fit with the model. This indicates that the teacher-made test items agree with an achievement test's characteristics.